2022
DOI: 10.1111/jcpe.13610
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, multicentre study of 6‐mm short implants in posterior alveolar bone supporting splinted crowns: A 5‐year follow‐up study

Abstract: Aim To evaluate the clinical and radiographic outcomes of 6‐mm short implants, placed in the posterior jaws and supporting splinted crowns, at 5 years after early loading. Materials and Methods Forty‐five patients with 95 implants (diameter: 4 mm; length: 6 mm) were enrolled at three centres. Two to three implants were placed in either the maxillary or the mandibular posterior region in each patient and restored with screw‐retained splinted crowns at 6 weeks later. Clinical and radiographic outcomes were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…And it is interesting to noticed that the mean marginal bone level changes were bone gain instead of bone loss in both groups in the present study. These ndings were consistent with previous studies of Bicon locking-taper implants (28, 29 Peri-implant bone gain of other implant systems also had been reported (30)(31)(32)(33). Blanes et al reported 43.8% of ITI posterior dental implants experienced some bone gain after 5 to 10 years follow-up (30).…”
Section: Discussionsupporting
confidence: 90%
“…And it is interesting to noticed that the mean marginal bone level changes were bone gain instead of bone loss in both groups in the present study. These ndings were consistent with previous studies of Bicon locking-taper implants (28, 29 Peri-implant bone gain of other implant systems also had been reported (30)(31)(32)(33). Blanes et al reported 43.8% of ITI posterior dental implants experienced some bone gain after 5 to 10 years follow-up (30).…”
Section: Discussionsupporting
confidence: 90%
“…Yoo et al [ 30 ] documented crestal bone gain around immediately loaded locking-taper Bicon implants, with five implants gaining > 2 mm. Peri-implant bone gain has also been reported with other implant systems [ 31 34 ]. In Blanes et al [ 31 ], 43.8% of ITI posterior dental implants exhibited bone gain after 5–10 years of follow-up.…”
Section: Discussionmentioning
confidence: 74%